THE EFFECT OF COMPANY AGE ON IMPRESSION MANAGEMENT PRACTICES - Purwitasari, Fadilla; Ariska, Ricky A.; Yustie, Renta (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: In order to maintain a good image in front of investors and other stakeholders, companies carry out impression management. Various factors are considered to influence how impression management practices are carried out by companies. One of these factors is the age of the company. This study aims to explore how the age of the company affects the impression management practices carried out by the company. Method: This study is a quantitative study with a data processing method of regression analysis. The research sample was 100 non-financial companies with the oldest and youngest ages listed on the Indonesia Stock Exchange in 2023. Impression management practice data was taken from the board of directors' report in the company's annual report and processed using the content analysis method. Results: The results of the study indicate that the age of the company does not affect the impression management practices carried out by the company. Novelty: There has never been any research in Indonesia that uses company age as a factor influencing impression management practices.